British defense policy against ISIL in Iraq and Syria under David Cameron 2014-2016 - Akila Paravathi P (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The purposes of this research to investigate how the UK's decision to engage militarily against ISIL, under Operation Shader, aligns with the principles of neoclassical realism. This research employs a qualitative methodology. The qualitative descriptive approach employed is one of data analysis. This approach is not limited to the presentation of numerical or statistical data. Instead, it focuses on the interpretation and description of the phenomenon under investigation, employing a narrative format. This approach prioritizes the collection of empirical evidence derived from observational studies, interviews, and the analysis of various documents. The results are how UK and US continues to defend itself against ISIL's presence and movements and seeks new strategies to drive them out of the international system.